Pemeliharaan Kubikel 20 KV di PT.Haleyora Powerindo - Johan Hidayat; Muhammad Fatkhurrokhman (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Maintenance of 20 kV cubicles at PT. Haleyora Powerindo is a crucial step in ensuring the reliability and safety of the electrical distribution system. This process includes preparation stages such as inspecting work equipment, coordinating power outages, and utilizing safety equipment (PPE) to minimize the risk of accidents. Subsequent steps involve voltage disconnection, verifying zero voltage using detection tools, cleaning components with specialized fluids, and drying to ensure that moisture does not cause disruptions. Once all stages are completed, the voltage is carefully reactivated, and a maintenance report is prepared to document the process. This study employs direct observation, interviews, and document analysis to evaluate the maintenance implementation and provide recommendations for quality improvement. The results are expected to serve as a guide for other companies in enhancing the efficiency and reliability of 20 kV cubicle maintenance to ensure a stable electricity supply.